Happiness : A Very Short Introduction - Haybron, Daniel M. (Oxford Oxford University Press, 2013)
Most of us spend our lives striving for happiness. But what is it? How important is it? How can we (and should we) pursue it? In this Very Short Introduction Dan Haybron provides a comprehensive look at the nature of happiness. By using examples, Haybron considers how we measure happiness, what makes us happy, and considers its subjective nature.
Include Illustrations, References and Index.
A Very Short Introduction.
Keywords: Happiness